(untitled) (Світ фінансів, 2017)
Козюк В. В. Макротеоретична етимологія фіскальних правил. Доведено, що етимологічно запровадження фіскальних правил коріниться у положеннях нової класичної макроекономіки. Показано, що прямі аналогії з динамічною інконсистентністю монетарної політики є обмеженими внаслідок відмінної природи реалізації владних повноважень урядом і центральним банком. Стверджується, що фіскальні правила є більш транспарентним критерієм ідентифікації дій політиків, особливо у випадках, коли альтернативні макротеоретичні концепції допускають суттєві відмінності в оптимальних траєкторіях державного боргу. Показано, що фіскальні правила можуть ефективно впливати на обмеження фіскального опортунізму, хоча і не гарантують повне його усунення. Козюк В. В. Макротеоретическая этимология фискальных правил. Доказано, что этимологически введения фискальных правил коренится в положениях новой классической макроэкономики. Показано, что прямые аналогии с динамической инконсистентность монетарной политики ограничены в силу разной природы реализации властных полномочий правительством и центральным банком. Утверждается, что фискальные правила усть более транспарентным критерием идентификации действий политиков, особенно в случаях, когда альтернативные макротеоретические концепции допускают существенные различия в оптимальных траекториях государственного долга. Показано, что фискальные правила могут эффективно влиять на ограничения фискального оппортунизма, хотя и не гарантируют полного его устранения. Kozyuk V. Macrotheoretical etymology of fiscal rules. The macroeconomic policy structural reforms that have being taking place during last 20 years show fundamental tendency to enhance institutional mechanisms of policy oriented on stability, efficiency and decrease vulnerability to external shocks. Fiscal policy regime switch basing on rules backgrounds often followed successful reforms of central banks. Large difference between political nature of monetary and fiscal decision-making is looked as a important driving force of additional macroeconomic considerations in direction to fiscal discipline. New sources of fiscal vulnerability in the long-run (aging, contingent liabilities, tax competition etc…) are looked as important drivers of fiscal discipline institutional protection. Empirical results show that there are some relations between fiscal rules design and fiscal discipline, but sometimes rule-based fiscal policy is not a guarantee against debt vulnerability. European debt crisis is good example of fiscal rules fragility. In some case, numerical rule for debt to GDP limit may be frustrated though lost motivation to decrease debt level down from committed point opening the door for loosening fiscal flexibility during trouble times. So, macroeconomic validation of fiscal rules is background for rational choice to have more disciplined deficit policy. Aside of applyability of dynamic inconsistency approach on fiscal rules, it is clear that differences between monetary and fiscal policy provide additional considerations about fiscal vulnerabilities. It is highlighted that most differences between monetary and fiscal policy from rules-based policy approach related to: short- and long-term effects of fiscal and monetary responds; differences in lags length; globalization influence on numerical target; possibilities to manipulate with numerical target; understanding what is efficiency of policy and what is outcome of efficient policy etc. Dynamic inconsistency theory shows fragility on the level of decision making. But social incentives to have stable fiscal environment should be based on understandings of risks for macroeconomic stability from unstable debt path and discretion over deficits. Market discipline fail is important driving force why fiscal policy should be restrained by rules. The more wide approach on fiscal policy efficiency is the more fragile is incentive structure on the level of decision making. Fiscal rules in this respect are viewed as important part of compensation of market fails and political opportunism. Wider understanding of what is efficient fiscal policy relative to monetary policy is viewed as prominent validation of why fiscal policy should be rules-based.